Determining Factors Of The Spatial Distribution Of Sumatra Elephant Track Activities in Pemerihan Resort Bukit Barisan Selatan National Park - Irma Kusuma Ningrum; Yanto Santosa (Department of Forest Resources Conservation and Ecotourism - IPB University, 2022)
The movement of Sumatran elephants from forests to villages and agricultural lands triggers elephant-human conflicts. The increase in conflict between Sumatran elephants and humans has caused a drastic decline in the Sumatran elephant population. The decline in the Sumatran elephant population indicates the importance of the conservation efforts carried out on the results of research studies related to the traces of Sumatran elephant activities. This study aims to analyze the relationship between activity traces and the characteristics of the Sumatran elephant habitat at Pemerihan Resort. The research was carried out from July 2021 to January 2022. The direct observation carried out in the observation line is 1 km long and 250 m wide (4 transect lines) with 4 repetitions. The results showed that the spatial distribution of Sumatran elephant activity traces is related to habitat characteristics, namely land cover type (secondary forest), topographic class (flat), distance from water sources (<1000 m), and distance from settlements (1000-2000 m). Traces of activity can be interpreted as an indicator of knowing the presence of Sumatran elephants that can prevent and minimize conflict levels. Management of the habitat and population of Sumatran elephants through enrichment of feed and captive activities is needed as a form of Sumatran elephant conservation efforts. Keywords: activity traces, habitat, Pemerihan Resort, Sumatran elephant